Comparison of treatment of hypokalemia with oral administration of potassium chloride vial or oral tablets - Leila Sabetnia; Farzaneh Hematian; Hosein Jafari; Reza Ganji; Ahmad Nezhadisalami (Journal of Nephropathology, 2024)
Introduction: Treatment of mild to moderate hypokalemia is a high potassium-containing diet and oral pharmaceutical potassium products. However, several medical centers in Iran use injectable dosage forms orally, which is not a confirmed method by reliable guidelines. Objectives: This study investigated the advantages and side effects of oral tablets versus injection vials of potassium chloride orally. Patients and Methods: This descriptive-analytical cross-sectional study was performed from March 2022 to June 2022. Thirty patients received tablets ("potassium chloride tablet" group), and thirty patients received injection vials ("potassium chloride vials orally" group) of potassium chloride orally. The variables, including age, gender, clinical side effects, and serum level of potassium, were regularly recorded. Results: The mean duration of serum potassium normalization was 42.00 hours for the "potassium chloride tablet" group and 84.57 hours for the "potassium chloride vials orally" group. The mean total potassium intake was 127.20 mEq/L in the "potassium chloride tablet" group and 280.03 mEq/L for the "potassium chloride vials orally" group. No significant difference was observed in gastrointestinal complications, including esophagitis, bloating, stomach ache, and nausea. None of the patients have required endoscopy due to esophagitis. Conclusion: Our result suggested that prescribing oral potassium chloride tablets has superior benefits over injection vials. However, more detailed research is needed to reveal the other aspects of this problem. Study Registration: This study was retrospectively registered in Research Registry UIN (UIN: reviewregistry1668).